Queer Exhibition Histories. - Hendrikx, Bas (Amsterdan : Valiz, 2023)
Tawanda Appiah, Aaron Betsky, Boudry/Lorenz, Övül Durmuşoğlu, Aleksandra Gajowy, Halyna Hleba, Jessica Gysel, Bas Hendrikx, Kateryna Iakovlenko, Valentina Iancu, Katrin Kivimaa, Rían Kearney, Leonida Kovač, Léon Kruijswijk, Élisabeth Lebovici, Edwin Nasr, Peaches, Katarina Pirak Sikku, François Piron, Rebeka Põldsam, Karol Radziszewski, Sylvia Sadzinski, Sara Salminen, Airi Triisberg, Eugenio Viola, Liang-Kai Yu
Queer Exhibition Histories comprises case studies highlighting the countless efforts, both large and small, of LGBTQIA+ artists and curators, centring on queer art exhibitions and their modes of documentation and archiving. Often, the legacy of these projects largely depends on personal archives, memories, and paraphernalia, with the overriding notion, or need, for public display. In these contexts, ‘public’ is relative in events that were either short-lived, held under the veil of domestic spaces, or kept exclusive for those ‘in the know’. Therefore, they were not exclusively artistic, but could equally be discursive, activist, educational, or serve as a tool for community building. At the intersection of queerness and contemporary art, this volume considers how the efforts of LGBTQIA+ artists have advanced their public presence in museums and society alike. [provided by publisher]
boek